Becoming Brothertown : Native American Ethnogenesis and Endurance in the Modern World - Cipolla, Craig N., 1978- (Book collections on Project MUSE., 2013)
In this book, the author follows the Brothertown Indians and their predecessors across New England, New York, and Wisconsin, disregarding the rigid cultural essences often associated with colonial histories in search of a deeper understanding of colonial culture and Native American identity politics from the eighteenth century to the twenty-first. -- Provided by publisher.